RİNOPLASTİ’DE DEPRESÖR SEPTİ NAZİ KASI REPOZİSYONUNUN HAFİF GÜLME DEFORMİTESİNE ETKİSİ - BENLİER, Erol; TOP, Hüsamettin; AYGIT, A. Cemal (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The nasal tip tends to rotate inferiorly during smiling, columella folded in width and the central upper lip moves superiorly. One of the most important factors that cause smiling deformity is hyperactivity of depressor septi muscle. Materials and Methods.- Between January 2000 and December 2002, depressor septi muscle was cut during standard rhinoplasty procedure in sixteen cases. Fourteen cases were female, other 2 were male. The age of cases was between 18 and 42 (mean age was 27). Depressor septi muscles were cut and inferior ends were sutured together in anterior and inferior position of anterio nasal spine. All patients were satisfied with aesthetic results. This procedure prevented the rotation of the nasal tip inferiorly. We have not seen any wound problem or shortening of frenulum. Results.- We conclude that the cutting of the depressor septi nasi muscle created a wider nasolabial angle. This procedure prevents to the forces that draws nasal tip inferiorly in mild smiling deformity.